2018
DOI: 10.1111/dom.13592
|View full text |Cite
|
Sign up to set email alerts
|

Of mice and men: Is there a future for metformin in the treatment of hepatic steatosis?

Abstract: Funding information LH is a BHF Senior Research Fellow in BasicScience. There is no project grant funding associated with this review.Non-alcoholic fatty liver disease (NAFLD) encompasses a spectrum of liver diseases, of which the first stage is steatosis. It is one of the most common liver diseases in developed countries and there is a clear association between type 2 diabetes (T2DM) and NAFLD. It is estimated that 70% of people with T2DM have NAFLD and yet there is currently no licensed pharmacological agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 112 publications
(220 reference statements)
2
26
0
Order By: Relevance
“…As individuals with T2DM typically have IHTAG accumulation, several studies have investigated the therapeutic effects of pharmacological agents and their effect on IHTAG content 157 . Briefly, these studies report that insulin-sensitising agents, including metformin and sulphonylureas, do not seem to decrease IHTAG content in humans, in contrast to the effects of metformin on reducing IHTAG levels in rodents 158 . Thiazolidinediones, which are selective ligands of the PPARs (of which there are α, β/δ and γ forms), seems to decrease IHTAG content 157 .…”
Section: [H1] Therapeutic Targetsmentioning
confidence: 99%
“…As individuals with T2DM typically have IHTAG accumulation, several studies have investigated the therapeutic effects of pharmacological agents and their effect on IHTAG content 157 . Briefly, these studies report that insulin-sensitising agents, including metformin and sulphonylureas, do not seem to decrease IHTAG content in humans, in contrast to the effects of metformin on reducing IHTAG levels in rodents 158 . Thiazolidinediones, which are selective ligands of the PPARs (of which there are α, β/δ and γ forms), seems to decrease IHTAG content 157 .…”
Section: [H1] Therapeutic Targetsmentioning
confidence: 99%
“…Furthermore, based on the closed correlation between excessive fructose intake, insulin resistance, and NAFLD, several studies indicated that metformin, an AMPK activator, might have therapeutic potential on liver steatosis [30]. Moreover, data obtained by increasing number of works suggest how SGLT2 inhibitors are an attractive option for NAFLD pharmacologic management [31].…”
Section: Representative Immunoblots Are Shownmentioning
confidence: 99%
“…Metformin primarily targets the liver, inhibiting lipogenesis and increasing fatty acid oxidation; therefore, a beneficial effect on liver lipid and fibrosis with metformin has been assumed. 33 However, comprehensive meta-analyses of randomised clinical trials concluded that reduction in both steatosis and fibrosis with metformin were underwhelming. 34 35 Liver fibroscan measure is repeated after 6 months of treatment.…”
Section: Methodsmentioning
confidence: 99%